How do community based dementia friendly initiatives work for people with dementia and their caregivers, and why? A rapid realist review. (6th December 2021) - Thijssen, Marjolein; Daniels, Ramon; Lexis, Monique; Jansens, Rianne; Peeters, José; Chadborn, Neil; Nijhuis‐van der Sanden, Maria W. G.; Kuijer‐Siebelink, Wietske; Graff, Maud
Abstract: Objectives: To describe and explain the outcomes of community dementia friendly initiatives (DFIs) for people with dementia and their caregivers to inform the development and tailoring of DFIs. Methods: Literature searches on DFIs were performed through two systematic online database searches of PubMed, Embase, ASSIA, CINAHL and Google scholar. Papers were only included if they evaluated outcomes using empirical data from people with dementia or caregivers. Data collection and analysis were guided by the categorization in the DEM‐FACT taxonomy and RAMESES guidelines for realist reviews. Results: Of 7154 records identified, 22 papers were included with qualitative, mixed method and quantitative study designs. The synthesis led to a description of programme theories addressing caring, stimulating and activating communities. Outcomes for people with dementia and caregivers included having contact with others, enjoyment and decrease of stress and, lastly, support. This synthesis also indicated how people with dementia participated in a specific role in DFIs, such as patient, team member or active citizen. Conclusions: DFIs generate different outcomes for people with dementia and caregivers, depending on the kind of initiative and the specific role for people with dementia. These findings could be a catalyst for initiation and further development of DFIs in a dementia friendly community (DFC). This draws attention to the multiple aspects of DFCs and supports reflection on their essential principles. Key points: This is the first synthesis of the outcomes and mechanisms of dementia friendly initiatives (DFIs) using studies with empirical data from the perspective of people with dementia or caregivers. DFIs generate different outcomes for both people with dementia and caregivers. DFIs have different outcomes for people with dementia participating in different specific roles (i.e. patient, team member or active citizen). DFI outcomes according to people with dementia and caregivers support both the practical development and research of how dementia friendly communities (DFCs) succeed in fulfilling their purpose.